Pengaruh Intensitas Aset Tetap, Sales Growth Dan Kepemilikan Institusional Terhadap Tax Avoidance - Sabila Dearty Rahmadhani; Eka Rima Prasetya (PT. Intelek Cendikiawan Nusantara, 2026)
This study aims to analyze the influence of Fixed Asset Intensity, Sales Growth and Independent Commissioners on Tax Avoidance. This research was conducted by analyzing the financial statements of companies in the Consumer Non-Cylicals sector on the Indonesia Stock Exchange (IDX) from the official website of the Indonesia Stock Exchange (IDX) during 2018-2024. The sample used in this study was 32 companies with a sample determination method using the purposive sampling method. The data used in this study is secondary data in the form of financial statements and annual reports from each company in the consumer non-cyclical sector which has been a research sample. The variables used in this study are Fixed Asset Intensity, Sales Growth and Independent Commissioners as independent variables and Tax Avoidance as dependent variables. The results of the study show that the best selected model to be used in this study is the Fixed Effect Model (FEM). The results of this study show that Fixed Asset Intensity has an effect on Tax Avoidance, Sales Growth has an effect on Tax Avoidance, and Independent Commissioners have no effect on Tax Avoidance and simultaneously Fixed Asset Intensity, Sales Growth, and Independent Commissioners have an effect on Tax Avoidance